Construction and structural evaluation of Viral Protein 7 of African horse sickness virus as a particulate, multiple peptide vaccine delivery system - Huismans, H. (Henk), 1942- (University of Pretoria, 2013)
Dissertation (MSc(Genetics))--University of Pretoria, 2005.